Вплив інгредієнтів автотранспортних викидів на стан пилку деяких квітникових рослин - Priymak, E.P.; Bessonova, V.P. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2007)
Influence of releases of motor vehicle on the dimen sions and fertility of pollen is analyzed. Results of use of flower plants pollen in phytoindication researches are presented. Flower plant species of street plantations for an evaluation of a degree of toxicity in a real complex of ecological factors are offered.